2020
DOI: 10.3390/met10091165
|View full text |Cite
|
Sign up to set email alerts
|

Melting and Flowing Behavior of Mold Flux in a Continuous Casting Billet Mold for Ultra-High Speed

Abstract: High casting speed coincides with the development trend of billet continuous casting, which significantly changes the casting characteristics. A mathematical model of the billet mold, which includes multiphase fluid flow, transient heat transfer, and solidification during ultra-high speed of the casting process was developed. The model is first applied to investigate the flow field of molten steel in the mold, studying the influence of steel flow upon the melting and flowing behavior of mold flux. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have reported flow‐heat transfer‐related phenomena in mold. Chen et al simulated the effect of casting speed, [ 14 ] SEN parameters [ 15 ] and mold flux properties [ 16 ] on the flow and heat transfer behaviors of mold molten steel and mold flux by establishing a 3D mathematical model and physical hydraulic experiment. [ 17 ] Sadat et al [ 18 ] investigated the effects of casting speed on the flow, heat transfer, and solidification in a mold by developing a 3D simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported flow‐heat transfer‐related phenomena in mold. Chen et al simulated the effect of casting speed, [ 14 ] SEN parameters [ 15 ] and mold flux properties [ 16 ] on the flow and heat transfer behaviors of mold molten steel and mold flux by establishing a 3D mathematical model and physical hydraulic experiment. [ 17 ] Sadat et al [ 18 ] investigated the effects of casting speed on the flow, heat transfer, and solidification in a mold by developing a 3D simulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to choose the appropriate melting point of mold flux, which has great influence on the efficiency of the continuous casting process. When the melting point of the mold flux is too large, the liquid flux layer may be too thin, and the steel leakage accident may occur [20][21][22][23] . The melting point of the mold flux can be changed by adjusting the type and content of mineral raw materials.…”
Section: Results and Discussion 31 Effect Of Mineral Raw Materials On...mentioning
confidence: 99%